Limites ao compartilhamento de prova no processo penal - Flores, Marcelo Marcante (2017)
The present study aims to discuss the limits for the evidence sharing in criminal action, focusing on the individual while subject of rights and not a mere object of investigation as the perspective for the analysis. Especially regarding the increment in the new ways of obtaining evidence, which provide a substantial change in the way one should look at the preliminary investigation and the production of the evidence under the contradictory scrutiny. In the Brazilian criminal action context, the understanding of the Superior Courts does not face the issue of evidence sharing with the necessary depth, which is why it has been admitted in an unlimited and unrestricted way. Thus, forensic praxis has been seeing the evidence sharing procedure - between criminal actions or even between criminal process and inaction of a different nature - without following the evidence prohibitions established by constitutional and infraconstitutional legislation. The evidence sharing discussion should observe that the introduction of new ways of obtaining evidence entails a (re)discussion on its general theory and its guiding principles. Evidence prohibition must be respected, and usurping these parameters by transversal routes (the sharing of evidence) cannot be allowed when there is violation of the subject’s fundamental rights. The study of the subject also passes through the valuation of fortuitous knowledge, which means, when and under what circumstances the information obtained in a criminal investigation can be used (shared) with another process of criminal nature as well. However, the discussion about sharing evidence is not restricted to fortuitous knowledge, once it covers other situations. Thus, the doctrinal discussion about the borrowed evidence also takes over great importance, as it is a starting point for the definition of some minimum standards. Nevertheless, one should observe that the legal categories discussed in the scope of the borrowed evidence do not provide enough subsidies to delimit the situations in which evidence is obtained by invasive methods in relation to fundamental rights, it is necessary to go further in this aspect from the comparative legislation and the established principles discussion. The construction of these minimum standards to delimit the hypotheses in which sharing shall happen (or not) has as basis the treatment of the individual as a subject of rights and not merely the object of the investigation, in order to establish a direction for the judicial valuation for the Brazilian criminal proceedings situations.